(3JGQjN GdNeSjfs - (3MSjf Hf eMeO Hf MSfs ((3jMi GdcGJH s)
(3ChdgG (B:s
(3GdehWf GdNGeS ai hbGFY GdfSI GdNGeSI ef GdgLQI (B" (3bhdg (B: (3ef ac SdjeGf Yf GdQb , hZRhI hOeI GdLfOd s
(3BNQgG (B:s
(3hJSdWGf hdOg GdSdWGf Sdje Hf SdjeGf SHY Sfjf hJhai SfI EKfjf hKeGfjf hJSYheGFI , hJSdWf hdOg GdSdWGf eQGO NGf fUQg Gddg ai GdJGQjg GdePchQ hGddg JYGdi CYde GdUhGH s
(3HgG fXGe GdJYbjHIs
(3bWYI efg (B_ (3cJH YdjgG CfgG GdfUa GdKGfis
(3cJHJ HQSe GdCejQ YHO GdbGOQ s
(3cJHJ GdYfGhjjf hHYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs